Fórmulas de saludo en la historia del español - Zielinski , Andrzej (El Colegio de México, 2025)
The purpose of this article is to study the greeting formulae that are recorded at different times in the history of the Spanish language; understood as discursive units, typical of the expressive speech act, these formulas serve to open the communicative channel of emerging social relations. From a usage-based approach and through a systematic search in electronic corpora (CORDE, BREPOLIS, eMGH), the study delves into 1) the paradigmatic origin of each of the formulae, 2) the sociopragmatic factors that discriminate its use and 3) its sociocultural distribution in different periods in the history of the Spanish language.